C Programming Language Still Ruling the World (Global Journal of Computer Science and Technology, 2022)
Abstract-C Programming Language, developed by Dennis Ritchie in 1972 is an evergreen programming language. It is the backbone of the Unix operating system and paved the way for the development of object-oriented programming. C has been around for 30 years, and there is a ton of source code available. This means there's a lot to learn from, and a lot to use. C programming language is that which sits close to the operating system. This feature makes it an efficient language because system level resources, such as memory, can be accessed easily. This language has features like it is a fast, flexible, portable and structured programming language having a rich library making the C programming language not to have an expiry date.
Keywords: language; programming; importance